1996
DOI: 10.1007/bf01271257
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of harman and norharman in cerebrospinal fluid of Parkinsonian patients

Abstract: Death of dopaminergic neurons in Parkinson's disease (PD) may partially be caused by synthesis and accumulation of endogenous and exogenous toxins. Because of structural similarity to MPTP, beta-carbolines, like norharman and harman, have been proposed as putative neurotoxins. In vivo they may easily be formed by cyclization of indoleamines with e.g. aldehydes. For further elucidation of the role of beta-carbolines in neurodegenerative disorders harman and norharman levels in cerebrospinal fluid (CSF) were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
2
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 14 publications
2
43
2
2
Order By: Relevance
“…Norharman, harman, 2-Me-norharmanium, and 2,9-(Me) 2 -norharmanium were found in the human brain and/or the CSF. A neurotoxic 2,9-dimethylated beta-carbolinium ion (2,9-(Me) 2 -norharmanium) was found in half of the PD, but not at all in non-PD, patients examined (Matsubara et al, 1995;Kuhn et al, 1996). These results suggest that beta-carbolinium compounds as well as isoquinolinium compounds may also be candidate neurotoxins that produce PD.…”
Section: Neurotoxic Substances Producing Pd In Humans and Animalsmentioning
confidence: 74%
“…Norharman, harman, 2-Me-norharmanium, and 2,9-(Me) 2 -norharmanium were found in the human brain and/or the CSF. A neurotoxic 2,9-dimethylated beta-carbolinium ion (2,9-(Me) 2 -norharmanium) was found in half of the PD, but not at all in non-PD, patients examined (Matsubara et al, 1995;Kuhn et al, 1996). These results suggest that beta-carbolinium compounds as well as isoquinolinium compounds may also be candidate neurotoxins that produce PD.…”
Section: Neurotoxic Substances Producing Pd In Humans and Animalsmentioning
confidence: 74%
“…Carbolinium ions have been found in the human brain and have been discussed as endogenous causative factors of PD (Matsubara et al 1993). Kuhn et al (1996) suggested that β-carbolines such as harmane and norharmane might be neurotoxins causing PD. Gearhart et al (2002) found β-carboline 2N-methyltransferase activity in the mammalian brain.…”
Section: Discussionmentioning
confidence: 99%
“…These include several isoquinoline and β-carboline species, which bear a strong structural resemblance to MPTP/MPP + . β-carboline [81] and tetrahydroisoquinoline (TIQ) species [93] have been isolated from the brain (particularly from the nigrostriatal system) [79] and CSF of IP patients, while Kuhn et al [72] reported increased plasma and CSF levels of the β-carbolines harman and norharman in IP patients. Such molecules, which have long been implicated in processes associated with alcohol and opiate addiction [40], exhibit to varying degrees a number of relevant cytotoxic properties, including uptake by dopaminergic neurons, impairment of mitochondrial function and induction of dopaminergic cell degeneration [24,59,82,92].…”
Section: Neuromelanin (Nm)mentioning
confidence: 99%